Implementation of Massage Efflaurage Method To Reduce Labor Pain During The Active Phase I - Wulan, Sri (JURNAL PENGMAS KESTRA (JPK), 2023)
Childbirth is normal in every pregnant woman, but many pregnant women cannot bear the pain during normal labor. Severe labor pain if not treated immediately can endanger the mother because it can cause the mother's condition to become unstable so that it can cause labor complications. Many methods can be done to reduce labor pain, one of which is the massage effleurage method, this method is very easy to apply, does not require expensive costs and can be done directly by mothers who give birth or family. How to do this method is by giving massage or soft touch on the mother's abdomen above the symplysis until it goes to the fundus and the right and left sides of the mother's abdomen are done repeatedly when contractions come. This community service implementation activity is carried out to increase the knowledge of pregnant women in preparing for childbirth, especially in overcoming labor pain when I. The activity was carried out in March 2023 at the obstetrics polyclinic of Granmed Lubuk Pakam Hospital, the participants of the activity were all pregnant women who visited ANC at Grandmed Hospital as many as 27 people, before being given implementation the majority of participants did not know about the massage effleurage method and after being given 100% implementation (27 people) participants could do massage effleurage. It is hoped that with the holding of this community service activity, pregnant women can have a more mature preparation to carry out normal labor and it is recommended that they can apply it during normal labor, especially during labor.